Tinjauan Hukum Islam Tentang Praktik Kerjasama Produksi Kopi Antara Perusahaan Dan Pengelola (Studi Kasus Di Desa Cikandang Kecamatan Cikajang) - Gausian, Gini; Maulana, Rakka Riandi (Jurnal Hukum Ekonomi Syariah, 2023)
Coffee is one of the large plantation commodities in Indonesia, although coffee plants are not from Indonesia. Almost thousands of hectares of land in Indonesia are planted with coffee both by the community and the Indonesian government which is a relic of Dutch colonialism. The development of coffee in Indonesia from year to year has a very rapid development because of information on the quality and benefits of coffee known to consumers. The formulation of the problem is: 1. How is the implementation of the practice of coffee production sharing cooperation carried out by the people of Cikandang village, Cikajang district, Garut regency? 2. What is the review of Islamic law regarding the coffee production cooperation agreement between the company and the manager? Researchers using library research is a type of qualitative research that is generally carried out by not going into the field in the search for data sources. The results of research from the Review of Islamic Law on the Practice of Coffee Production Cooperation Between Companies and Managers, namely Shari'a, allow this profit-sharing cooperation so that each of the two benefits. The profit sharing of coffee production cooperation is also useful, especially for capital owners and general managers of the Cikandang Village community who are involved in coffee plantations to their production, and the contract used is a mudharabah contract. Keywords: Cooperation, Production, Contract, Islamic Law